Identification of growth hormone gene variation in exon region at Indonesian Local Cattle based on PCR-SSCP method - SURYA NUR RAHMATULLAH; JAKARIA JAKARIA; RONNY R NOOR (Biodiversitas Journal of Biological Diversity, 2016)
Rahmatullah SN, Jakaria, Noor RR. 2016. Identification of growth hormone gene variation in exon region at Indonesian Local Cattle based on PCR-SSCP method. Biodiversitas 17: 492-497. The aim of this study was to identify the polymorphisms of the growth hormone gene (GH) of Indonesian local cattle as well as two exotic cattle, as the outside group, using polymerase chain reaction and single strand conformation polymorphism (PCR-SSCP) and using five primers DNA to identify polymorphism of GH gene. Twenty DNA samples of each Indonesian local cattle, consists of Bali, Pesisir, Madura and Katingan, and ten DNA samples of Simmental and Limousine cattle were used. The results showed that the polymorphism of the GH gene was found in three exons which are exon 1, 2 and 5 for Indonesian local cattle except for the Bali and Madura cattle that showed polymorphism was only at exon 2. Bali and Madura cattle also showed monomorphism in exon 3 and 4. On the other hand, the exotic breed showed the polymorphism in all exons, except for exon 2 in Simmental cattle which was found to be monomorphic.